Long-term effects of rent supplements and mental health support services on housing and health outcomes of homeless adults with mental illness: extension study of the At Home/Chez Soi randomised controlled trial. (November 2019) - Stergiopoulos, Vicky; Mejia-Lancheros, Cilia; Nisenbaum, Rosane; Wang, Ri; Lachaud, James; O'Campo, Patricia; Hwang, Stephen W
Summary: Background: Housing First is increasingly implemented for homeless adults with mental illness in large urban centres, but little is known about its long-term effectiveness. The At Home/Chez Soi randomised controlled trial done in five cities in Canada showed that Housing First improved housing stability and other select health outcomes. We extended the At Home/Chez Soi trial at the Toronto site to evaluate the long-term effects of the Housing First intervention on housing and health outcomes of homeless adults with mental illness over 6 years. Methods: The At Home/Chez Soi Toronto study was a randomised, controlled trial done in Toronto (ON, Canada). Here, we present the results of an extension study done at the same site. Participants were homeless adults (aged ≥18 years) with a serious mental disorder with or without co-occurring substance use disorder. In phase 1, participants were stratified by level of need for mental health support services (high vs moderate), and randomly assigned (1:1) using adaptive randomisation procedures to Housing First with assertive community treatment (HF-ACT), Housing First with intensive case management (HF-ICM), or to treatment as usual (TAU). Participants with moderate support needs were further stratified by ethnoracial status. Considering the nature of the Housing First intervention, study participants and study personnel were not masked to group assignment. Phase 1 participants could choose to enrol in the extension study (phase 2). The primary outcome was the rate of days stably housed per year analysed in the modified intention-to-treat population, which included all randomly assigned participants who had at least one assessment for the primary outcome. Participants contributed data to the study up to the point of their last interview. Multilevel multiple imputation was used to handle missing data. The trial was registered with ISRCTN, ISRCTN42520374. Findings: Between Oct 1, 2009, and March 31, 2013, 575 individuals participated in phase 1 of the Toronto Site At Home/Chez Soi study (197 [34%] participants with high support needs and 378 [66%] with moderate support needs). Of the 378 participants with moderate support needs, 204 were randomly assigned to receive the HF intervention with ICM or with ethnoracial-specific ICM services (HF-ER-ICM; HF-ICM or HF-ER-ICM groups) and 174 were randomly assigned to TAU. Of the 197 participants with high support needs, 97 were randomly assigned to receive the HF intervention with ACT (HF-ACT treatment group) and 100 were randomly assigned to TAU group. Between Jan 1, 2014, and March 31, 2017, 414 (81%) of 575 phase 1 participants participated in the extended phase 2 study. The median duration of follow-up was 5·4 years (IQR 2·1–5·9). Among phase 2 participants, 141 had high support needs (79 participants in the HF-ACT group; 62 participants in the TAU group), and 273 had moderate support needs (160 participants in the HF-ICM or HF-ER-ICM group; 113 participants in the TAU group). 187 high support needs participants (93 participants in the HF-ACT group, 94 participants in the TAU group), and 361 moderate support needs participants (201 participants in the HF-ICM or HF-ER-ICM group, 160 participants in the TAU group) were included in the modified intention-to-treat analysis for the primary outcome. The number of days spent stably housed was significantly higher among participants in the HF-ACT and HR-ICM or HF-ER-ICM groups than participants in the TAU groups at all timepoints. For participants with moderate support needs, the rate ratio (RR) of days stably housed in the Housing First group, compared with TAU, was 2·40 (95% CI 2·03–2·83) in year 1, which decreased to 1·13 (1·01–1·26) in year 6. The RR of days stably housed for participants with high support needs, compared with TAU, was 3·02 (2·43–3·75) in year 1 and 1·42 (1·19–1·69) in year 6. In year 6, high support needs participants in the Housing First group spent 85·51% of days stably housed compared with 60·33% for the TAU group, and moderate needs participants in the Housing First group spent 88·16% of days stably housed compared with 78·22% for the TAU group. Interpretation: Rent supplements and mental health support services had an enduring positive effect on housing stability for homeless adults with mental illness in a large, resource-rich urban centre, with a larger impact on individuals with high support needs than moderate support needs. Funding: Mental Health Commission of Canada, Ontario Ministry of Health and Long-Term Care, and the Canadian Institute of Health Research.